Self-Induced Transparency Solitons and Dissipative Solitons in Microwave Electronic Systems - Ginzburg, N. S.; Zotova, I. V.; Kocharovskaya, E. R.; Sergeev, A. S.; Zheleznov, I. V.; Zaslavsky, V. Yu (Radiophysics and quantum electronics, 2021)
Solitons are a well-studied subject in many domains of nonlinear physics, including hydrodynamics, plasma physics, optics, etc. However, it has been demonstrated only recently that they can be realized in systems of microwave electronics. This review presents the results of analyzing theoretically the formation mechanisms of envelope solitons of two types. The first type is the self-induced transparency soliton, which is formed in the process of cyclotron-resonance interaction of electromagnetic pulses with initially rectilinear electron beams moving in a homogeneous magnetic field, and the relativistic dependence of the gyrofrequency on the particle energy is of fundamental importance for its formation. The second type is the soliton formed when saturable absorbers are installed in the feedback loops of electronic generators. Under such conditions, passive locking of resonator modes occurs, and the generated radiation is a periodic sequence of short pulses, which, on by analogy with laser systems, should be categorized as the class of dissipative solitons. Along with its general theoretical importance, the study of microwave solitons is of significant practical interest. In particular, experimental realization of generation of dissipative solitons in the microwave band will make it possible to create a new type of sources of ultrashort electromagnetic pulses.